Shaping your identity as a speaker of English: the struggles of a beginner language learner - Ortiz Medina, Janeth María (Colombian Applied Linguistics Journal, 2017)
In Colombia, political and educational campaigns have promoted English as the language of success and as a fundamental requirement to comply with the demands of a globalized world; nevertheless, little attention has been paid to the individual experiences of Colombians as they learn this language or to what happens to their identities during this process. This paper reports on a study that explored how three young adult learners of English constructed their identities as speakers of English through their positioning in oral tasks in an English class. It focuses on the story of one of the participants: a beginner female English learner. Data collection methods included class video and audio-recordings, interviews, and diaries kept by the participants. Findings indicated that learners’ positioning in spoken interactions not only directly affected their use of English, but also led them to non-linear transformations of their identities as speakers of English. These results pinpoint the need to gain awareness of the centrality of students’ identities in both their learning process and in language teaching practices and the need to observe how positioning operates in the language classroom.